2012
DOI: 10.1111/jbi.12048
|View full text |Cite
|
Sign up to set email alerts
|

Colonization history of Metrioptera roeselii in northern Europe indicates human‐mediated dispersal

Abstract: Aim The bush‐cricket Metrioptera roeselii is an example of an insect which has expanded its indigenous range beyond expectations based on its natural dispersal potential. Understanding how species colonize new areas is vital for formulating effective species conservation programmes and managing invasive species. The aim of this research is to use mitochondrial sequence and microsatellite data to delineate the likely origin and dispersal pathways of M. roeselii in northern Europe. The well‐known ecology of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
50
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(53 citation statements)
references
References 65 publications
(86 reference statements)
3
50
0
Order By: Relevance
“…Moreover, all the populations sampled in Corsica had the same allelic pools and were genetically not differentiated, suggesting one unique colonization event followed by a step-by-step local expansion between neighbouring host patches, as was shown for the Cedar seed wasp Megastigmus schimitscheki (AugerRozenberg et al, 2012). Similar findings of severe bottlenecks at introduction in different species suggested that successful invasions can also result from a very small number of original migrants, which is sometimes considered as a characteristic of successful invasive species (Kaň uch et al, 2013). Diverse genetic and/or ecological mechanisms may circumvent the loss of genetic variation occurring during introduction events (Lye et al, 2011; Auger-Rozenberg et al, 2012).…”
Section: Contrasting Colonization Processes In Different Invaded Regionsmentioning
confidence: 52%
See 3 more Smart Citations
“…Moreover, all the populations sampled in Corsica had the same allelic pools and were genetically not differentiated, suggesting one unique colonization event followed by a step-by-step local expansion between neighbouring host patches, as was shown for the Cedar seed wasp Megastigmus schimitscheki (AugerRozenberg et al, 2012). Similar findings of severe bottlenecks at introduction in different species suggested that successful invasions can also result from a very small number of original migrants, which is sometimes considered as a characteristic of successful invasive species (Kaň uch et al, 2013). Diverse genetic and/or ecological mechanisms may circumvent the loss of genetic variation occurring during introduction events (Lye et al, 2011; Auger-Rozenberg et al, 2012).…”
Section: Contrasting Colonization Processes In Different Invaded Regionsmentioning
confidence: 52%
“…The colonization of the northern Mediterranean coast was a pre-requisite for a successful invasion of Corsica, South-Eastern France acting as a 'bridgehead' , that is, as a new potential source population to reach new territories (Lombaert et al, 2010). A similar situation was observed for the bush cricket Metrioptera roeselii that crossed the Baltic Sea once introduced along the coast (Kaň uch et al, 2013). Larvae may be regularly transported from the French and Italian coasts to Corsica, but the probability of settlement is rather low, because the larvae need a suitable host to survive and found an invasive population.…”
Section: Contrasting Colonization Processes In Different Invaded Regionsmentioning
confidence: 75%
See 2 more Smart Citations
“…Although studies on phytophagous shield bugs similar to G. lineatum have shown that individuals move only short distances (mainly to the next food patch) a yearly range expansion estimate of 1.07 km is not surprising because of general differences between individual dispersal rates and species expansion rates. Species expansion is the sum of the movement dynamics of geographically distributed populations where extinction and colonization events are controlled both by species' ecology and the environment, and may not be directly predictable by individual movement patterns (Berggren et al 2009, Preuss et al 2011, Kaň uch et al 2013). …”
Section: Distribution Expansion and Reporting Biasmentioning
confidence: 99%